Fungsi Lembaga-Lembaga Pendidikan Islam - Aripuddin; Bahaking Rama; Ferdinan (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This study aims to analyze the functions of Islamic educational institutions in informal, formal, and non-formal pathways. The research employs a qualitative approach using a library research method by examining scholarly books and journal articles related to Islamic education. The findings indicate that informal Islamic education serves as the foundation for character building and religious values, formal Islamic education plays a role in developing students’ academic and professional competencies, while non-formal Islamic education functions as a reinforcement of Islamic understanding and community empowerment. The synergy among these three educational pathways is crucial in achieving holistic and sustainable Islamic education goals. AbstrakPenelitian ini bertujuan untuk menganalisis fungsi lembaga-lembaga pendidikan Islam pada jalur informal, formal, dan nonformal. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan terhadap berbagai sumber ilmiah yang relevan dengan pendidikan Islam. Hasil penelitian menunjukkan bahwa pendidikan Islam informal berfungsi sebagai fondasi pembentukan karakter dan nilai religius, pendidikan Islam formal berperan dalam pengembangan kompetensi akademik dan profesional peserta didik, sedangkan pendidikan Islam nonformal berfungsi sebagai penguat pemahaman keislaman dan pemberdayaan masyarakat. Sinergi antara ketiga jalur pendidikan tersebut menjadi faktor penting dalam mewujudkan tujuan pendidikan Islam yang holistik dan berkelanjutan.